2018
DOI: 10.1002/mp.13277
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a high‐sensitivity multi‐pinhole cardiac SPECT system with hemi‐ellipsoid detectors

Abstract: Purpose: Single-photon emission computed tomography (SPECT) is a noninvasive imaging modality, used in myocardial perfusion imaging. The challenges facing the majority of clinical SPECT systems are low sensitivity, poor resolution, and the relatively high radiation dose to the patient. New generation systems (GE Discovery, DSPECT) dedicated to cardiac imaging improve sensitivity by a factor of 5-8. This improvement can be used to decrease acquisition time and/or dose. However, in the case of ultra-low dose (~3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Bhusal et al (95) investigated a novel cardiac SPECT system consisting of 21 pinhole collimators, each coupled to a hemi-ellipsoid detector. They performed GATE simulations with various phantoms to evaluate the system performance.…”
Section: Hemi-ellipsoid Spectmentioning
confidence: 99%
“…Bhusal et al (95) investigated a novel cardiac SPECT system consisting of 21 pinhole collimators, each coupled to a hemi-ellipsoid detector. They performed GATE simulations with various phantoms to evaluate the system performance.…”
Section: Hemi-ellipsoid Spectmentioning
confidence: 99%
“…Space limitation, spatial resolution and sensitivity are determinant in collimator selection for a particular imaging task [14,11]. An appropriate collimator needs to be selected for a specific imaging application, for instance a fan or cone beam collimator for brain imaging, a pin-hole collimator for thyroid, and parallel-hole collimator as generally used in SPECT and planar imaging [7,20,26].…”
Section: Classification Of the Collimatorsmentioning
confidence: 99%
“…In a simulation, Zeng et al (70) demonstrated that multidivergent beam collimators could double the photon sensitivity of current SPECT camera systems without sacrificing spatial resolution. Simulations of multipinhole designs with paired curved paraboloid or hemi-ellipsoid detectors could improve photon sensitivity by up to 300% (71,72). In phantom studies, these designs have improved photon sensitivity and spatial resolution compared with published characteristics or commercially available solid-state camera systems (72).…”
Section: Future Hardware Designsmentioning
confidence: 99%
“…Simulations of multipinhole designs with paired curved paraboloid or hemi-ellipsoid detectors could improve photon sensitivity by up to 300% (71,72). In phantom studies, these designs have improved photon sensitivity and spatial resolution compared with published characteristics or commercially available solid-state camera systems (72). Nevertheless, these published reports are still preclinical, and it remains to be seen if these designs will be cost-effective and adequate for clinical implementation.…”
Section: Future Hardware Designsmentioning
confidence: 99%